Exploring the Application of Contrast‐Enhanced Ultrasound in ACR BI‐RADS 4A Lesions (≤ 2 cm): A Prospective Multicenter Study in China. - Xiao, Xiaoyun; Zhang, Wei; Luo, Xiaomao; Peng, Yulan; Zheng, Yanling; Zhou, Qi; Hu, Qiao; Zhu, Ying; Zhang, Heng; Li, Yinghua; Zhou, Qing; He, Wen; et al. (Breast Journal, 2026)
Purpose: To assess the added diagnostic value of contrast‐enhanced ultrasound (CEUS) in differentiating small breast lesions initially categorized as ACR BI‐RADS 4A. Materials and Methods: A total of 1595 patients with small breast lesions (≤ 20 mm) from 37 tertiary hospitals were enrolled from August 2021 to August 2022. B‐mode ultrasound, color Doppler, and CEUS were performed to evaluate the lesions. The integration of CEUS led to the reclassification of BI‐RADS 4A lesions into three pathways: upgrade to 4B, downgrade to 3, or no change in category. The diagnostic performance of CEUS was evaluated, and the contrast modes which could be used to correctly downgrade or upgrade BI‐RADS 4A lesions were explored. Results: A total of 1340 lesions were finally included in the analysis of CEUS performance. The average age of all included participants was 43 ± 8 (range from 20 to 84). The average diameter of the lesions was 12.4 ± 3.8 mm (range from 5 mm to 20 mm). The diagnostic performances of CEUS + BI‐RADS were 98.3% for sensitivity, 81.7% for specificity, 34.1% for positive predictive value, 99.8% for negative predictive value, and 83.1% for overall accuracy, respectively. The sensitivity was slightly downgraded (98.3% vs. 100%, p = 0.1555), while the specificity and accuracy were greatly elevated (p < 0.05). The receiver operating characteristic curve (ROC) value was calculated using a binary classification threshold, with BI‐RADS 3 as low‐risk and BI‐RADS 4A as high‐risk. The area under ROC was 0.896 (95% CI: 0.878, 0.911) for BI‐RADS + CEUS. The decision curve analysis showed that using CEUS + BI‐RADS to guide biopsy decisions provided net benefit compared to the default strategy of biopsying all lesions. Conclusion: The addition of CEUS allows for the correct downgrading of most benign BI‐RADS 4A lesions, thereby avoiding unnecessary biopsies. An upgrade from BI‐RADS 4A to 4B on CEUS warrants immediate biopsy to ensure prompt diagnosis and treatment. Trial Registration: Chinese Clinical Trial Registry: ChiCTR2100050719